Exploring Plasma Sources for Optimized Production of Metastable Atoms and Reactive Species - Alinka Vesel; Miran Mozetic; André Ricard (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
Flowing plasmas and afterglows sustained by DC glow, hollow cathode arc (HCA), and microwave (surfatron) discharges have been studied to obtain a maximum density of R (He, Ne, Ar) metastable atoms and N, O, and H atoms by setting the experimental parameters such as the gas pressure and mixture, the discharge tube diameter, gas flow rates, discharge power, etc. The absolute densities of these active species have been measured by resonant absorption spectroscopy, NO titration with emission spectroscopy, and a catalytic probe. The maximum densities of He (23S), Ne(3P2), and Ar(3P2) metastable atoms obtained in these discharges at reasonable powers or power densities are a few 1011-1012 cm-3 in the range of pressures between 0.1 and 1 Torr. The densities of N, O, and H atoms may be as large as 1015 – 1016 cm-3 in the pressure range between 0.1 and 10 Torr providing the surface of materials facing plasma exhibit a low coefficient for heterogeneous surface recombination. A dissociation fraction of oxygen atoms is often around 10% at reasonable discharge power, more in a mixture with a noble gas. The N-atom density is limited because of the high binding energy of nitrogen molecules and thus a rather poor production rate. The H-atom density tends to be limited by significant surface losses unless the experimental systems are made from quartz glass.